IDENTIFICATION AND CLASSIFICATION OF RISK IN QUALITY MANAGEMENT IN THE CASHEWN PRODUCTION PROCESS - Agita Muchammad Rozaqie; Arief Bimantoro Suharko (Jurnal Scientia, 2023)
PT TTO is classified as a new company, in terms of quality management it still does not have a strategy and professional standards for quality management, so research is needed to identify risks in quality management in cashew nut production. To produce consistent product quality to encourage the realization of the goals and values of the company . This study uses the interview method to obtain information related to risks in quality management and classify risk events from the pre-production stage, the production process stage and the post-production stage. Processing uses the calculation of Risk Priority Numbers by grouping risks based on the impact of the risk occurrence (Severity), the frequency of occurrence of the risk (Occurance), and the probability of the risk being detected before it occurs (D). Based on the calculation of the RPN value based on the production stages, namely the pre-production stage, the production process stage, and the post-production stage. Where at the time of calculating and ranking the risk agents, it was found that the pre-production stage had risk events and risk agents with the top order. That is, there is a discrepancy in raw material specifications due to crop failure by farmers in the first place (RPN value of 280) and raw materials sent by farmers are not in accordance with the opportunity (RPN value of 256). As for the next order at the stage of the production process with the risk of non-compliance with specifications due to errors in production labeling for grading and production date